Groundwater use and sustainability in Punjab agriculture: insights from a field survey - Kamal Vatta; Shruti Bhogal; Adam S Green; Cameron A Petrie; Heena Sharma; Sandeep Dixit (Agricultural Economics Research Review, 2023)
Paddy is a water-intensive crop, and its cultivation is the prime cause of the depletion of groundwater resources in Punjab. We survey paddy farmers’ crop choices, water use, and opinions on the causes of the depletion of groundwater resources. To make long-term groundwater use sustainable, farmers can adopt water saving technologies and practices and diversify crops. But adoption is abysmal, and diversification into alternative crops entails high production and marketing risks. To improve adoption, the government must promote water saving technologies and practices. And assured marketing at remunerative prices is a prerequisite for crop diversification.